Baricitinib: From Rheumatoid Arthritis to COVID‐19. (12th June 2021) - Assadiasl, Sara; Fatahi, Yousef; Mosharmovahed, Banafsheh; Mohebbi, Bahareh; Nicknam, Mohammad Hossein
Abstract: Baricitinib is a JAK1/2 inhibitor that was first approved for treating moderate to severe rheumatoid arthritis (RA) but that later showed considerable efficacy in the control of exaggerated inflammatory responses that occur in a wide range of diseases. There is a growing body of evidence, obtained from clinical trials and case reports, demonstrating clinical and paraclinical improvement in patients following administration of baricitinib including RA, systemic lupus erythematosus, psoriasis, atopic dermatitis, alopecia areata, interferon‐mediated autoinflammatory diseases, graft‐versus‐host disease, diabetic kidney disease, and, recently, coronavirus disease‐19. However, despite overall encouraging results, many adverse effects have been observed in baricitinib‐treated patients, ranging from simple infections to increased risk of malignancies, particularly in long‐term use. The significant efficacy of baricitinib, versus the probable adverse effects, urge further investigation before establishing it as a part of standard therapeutic protocols. Here, we have provided a review of the studies that have used baricitinib for treating various inflammatory disorders and summarized the advantages and disadvantages of its administration.